Virtual Reality Video as An Exhibition Design Idea in Response to The Covid Pandemic - Ranangsari, Kosalalita Anggiyumna; Marianto, Martinus Dwi; Dayani, Elin Siska (Journal of Urban Society's Arts, 2024)
Although the Covid-19 pandemic is still occurring in Indonesia in 2021, it does not become an obstacle for the artist to continue to innovate both creating and exhibiting their work. One of the innovations in organizing art activities is to switch the format from physical exhibitions to virtual exhibitions during the pandemic. The creation of the 360 video-based virtual exhibition “Estetika Sanggit” using 3D animation as a response to the pandemic is based on the concept of User-Centered Design. This research uses a descriptive-qualitative method with a phenomenological approach. The use of this methodology is to discuss the designer’s subjective experience in integrating multiplatform technology (3D animation, 360° video, and Virtual Reality) in designing a virtual exhibition that is “friendly” to visitors. The results of this research show that the designer succeeded in creating a 360° video virtual exhibition that greatly facilitates users in accessing and enjoying the virtual exhibition as if enjoying a physical exhibition. This is evident in the presentation of the virtual exhibition and is obtained from the positive impressions of visitors to this virtual video. These positive impressions demonstrate IDE Studio’s success in designing products that meet user needs. Meskipun pandemi Covid-19 masih terjadi di Indonesia pada tahun 2021, tidak menjadi penghambat bagi seniman untuk terus berinovasi baik berkarya maupun memamerkan hasil karyanya. Salah satu inovasi dalam menyelenggarakan kegiatan kesenian adalah beralih formatnya pameran fisik ke pameran virtual di masa pandemi. Penciptaan pameran virtual “Estetika Sanggit” berbasis video 360 dengan menggunakan animasi 3D sebagai respon menghadapi pandemi didasarkan pada konsep User-Centered Design. Penelitian ini menggunakan metode deskriptif-kualitatif dengan pendekatan fenomenologi. Penggunaan metodologi ini untuk membahas pengalaman subjektif desainer dalam mengintegrasikan teknologi multiplatform (3D animation, 360° video, dan Virtual Reality) pada perancangan pameran virtual yang “ramah” terhadap pengunjung. Hasil dari penelitian ini menunjukkan bahwa desainer berhasil menciptakan pameran virtual video 360 yang sangat memudahkan pengguna dalam mengakses serta menikmati pameran virtual tersebut layaknya menikmati pameran fisik. Hal ini tampak pada sajian pameran virtualnya dan didapatkan dari kesan positif para pengunjung video virtual ini. Kesan positif tersebut menunjukkan keberhasilan IDE Studio dalam merancang produk yang sesuai dengan kebutuhan pengguna.